PHQ-8 Days: a measurement option for DSM-5 Major Depressive Disorder (MDD) severity - Balluz Lina S; Strine Tara W; Zack Matthew M; Kroenke Kurt; Dhingra Satvinder S (BMC, 2011)
Abstract Background Proposed draft diagnostic criteria for the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) suggest that dimensional assessments can supplement dichotomous diagnoses by incorporating measures of severity, frequency, and duration, providing the ability to monitor changes in symptoms over time and to guide appropriate treatment. Methods This report is based on data from the Behavioral Risk Factor Surveillance System 2006 from 198,678 survey participants who responded to all eight Patient Health Questionnaire (PHQ-8) items. We evaluated use of the days version of the PHQ-8 to determine an optimal cut-point for identifying respondents with depression and to evaluate the performance characteristics of the PHQ-8 at this cut-point. Results A PHQ-8 score of 55 or more days was determined to be the optimal cut-point when compared to the DSM-derived PHQ-8 algorithm for a major depressive episode (five or more symptoms present "more than half the days," at least one of which must be anhedonia or depression). In the full sample, the sensitivity and the specificity of this cut-point were 0.91 (0.90-0.93) and 0.99 (0.99-0.99), respectively. Conclusion The days version of the PHQ-8 may be a valuable dimensional alternative to the traditional PHQ-8 by offering finer granularity of dimensionality (a score of 0 to 112).